Elucidative Histopathological Study in Female Cancer Patients: Histopathology in Female cancers - Tarannum, Juveria; Manaswini, P.; Deekshitha, Ch.; Reddy, B. Pratap; Sunder, A. Shyam (Iraqi Journal of Science, 2020)
Aims: Because of the high incidence of cancer in females, we need to identify an accurate therapy to deal with the treatment of different types and stages of cancer. Histopathology acts as an important step to foresee the stage in which the cancer is present, its risk of metastasis, and the health outcomes after completion of treatment. Histopathology grading acts as an important criterion to determine the treatment pattern to be adopted, the prognosis in patients and other possible future risks. Hence conducting novel histopathologcial studies in major female cancers is necessary in determining the treatment plan to be chosen for the patient.Study design: Retrospective Observational studyPlace and Duration of Study: St. Ann’s Cancer Hospital, Warangal, Telangana, India. The patient’s histopathological reports were collected between March and August 2018.Methodology: The study sample included 275 non-pregnant female patients aged above 20 years and diagnosed with different cancers based on histopathology. Histopathological observations were taken by collecting parameters that included specimen submitted, lymphadenopathy specimen, macroscopic appearance, macroscopic tumour site, coexistent pathology, histological tumour grade, lymphovascular invasion, and distant metastasis.Results: The histopathologcial study concludes that regional lymph nodes (55.2%) were more common than other lymph nodes. Mostly, tumours demonstrated swollen and ulcerative appearance (48%), with grading as G0 stage (57.45%) having better prognosis and good quality of life. The most commonly observed types of tumours were as follows; In Breast Cancer: infiltrating ducal carcinoma (61. 9%), in Cervix Cancer: squamous cell carcinoma (83.92%), in Ovarian Cancer: mucinous cystadenocarcinoma (53.84%), in Vaginal Cancer, and in Vulvar Cancer: squamous cell carcinoma (100%).Conclusion: Knowing the type of tumour to develop, the threat it poses to health, and the mechanisms that mediate its development are important factors in the management of the disease. This detailed information may aid the implementation of more accurate preventive measures in a population by selecting the proper treatment plan and understanding the risk of future chances of reoccurrence and metastasis.